Martí, Monologue, and the Metaphorical Dawn in Raúl de Cárdenas's Un hombre al amanecer - Bulman, Gail A. (Latin American Theatre Review, 2004)
Un hombre al amanecer by Cuban playwright Raúl de Cárdenas traces and reflects upon the life of nineteenth-century Cuban patriot and writer José Martí, the play’s only character. However, three dramatic techniques – the interweaving of four types of monologue, the juxtaposition of past and present, and the incorporation of Martí’s own writings into the play – move the play’s focus away from Martí and toward a more contemporary view of a Cuban writer’s relationship to his nation. This article examines the play’s complicated structure and shows how Cárdenas fuses multiple perspectives on Martí’s life and writings to expose his own ambivalent relationship with Cuba, a relationship that is as poignant to the present-day writer as it was for his nineteenth-century predecessor/protagonist (GAB).